PERAN STRATEGIS PEMERINTAH PROVINSI BALI DALAM PELESTARIAN BUDAYA LOKAL - Ida Bagus Gede Paramita; I Wayan Sudika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Nowadays Indonesian culture is considered increasingly lost direction as seen from the increasingly fading values ??of the nation's character. If it is said that Indonesian culture is increasingly lost direction, of course it also reflects local culture or regional culture where its existence is increasingly not seen in its social life. This situation is indisputable because in reality it did happen like that. As an example of one of the Balinese cultures, namely the Balinese language, although as the mother tongue of young Balinese children, many do not speak fluent Balinese. Therefore, conservation efforts are needed to avoid the disadvantageous things such as; claimed to be the culture of other regions or countries, extinct because no one has been the speaker, forgotten or not remembered by future generations, and the regions / countries will lose their identity, and so forth. To preserve local / regional culture, it cannot be done by the government alone or by the community alone, but must be done jointly by all stakeholders. It's just that the leading sector or the driving force is the government, especially local governments, because it has various facilities and access that can be utilized. Aware of the erosion of local culture (Bali) The Provincial Government of Bali is committed to inviting people to rise up to preserve Balinese culture which is suspected to be increasingly lost or increasingly forgotten. The seriousness of the Bali Provincial Government in preserving Balinese culture is reflected in its vision and mission. Through the implementation of the vision and mission which are further outlined in the work program of the Provincial Government of Bali, there are several strategic roles that can be carried out starting from the role as a cultural preserver to striving for optimal use of public space for the preservation of local culture / Balinese culture. Keywords: Cultural Preservation, Strategic Role, and the Provincial Government of Bali.